Stable isotopes (δ18O and δ13C), trace and minor element compositions of Recent scleractinians and Last Glacial bivalves at the Santa Maria di Leuca deep-water coral province, Ionian Sea - López Correa, Matthias; Montagna, Paolo; Taviani, Marco; Vendrell-Simón, Begona; McCulloch, Malcolm (Deep-Sea Research Part Ii-Topical Studies in Oceanography, 2010)
The aragonitic skeletons of bathyal cold-water corals have a high potential as geochemical in situ archives for paleoceanography. Oxygen isotopes and stable carbon isotopes (δ18O and δ13C) have been analyzed, as well as trace and minor element compositions (e.g. Mg/Ca, Sr/Ca, U/Ca, B/Ca and P/Ca) in Lophelia pertusa, one of the most important frame-builders at the Santa Maria di Leuca (SML) deep-water coral hotspot in the Central Mediterranean. The Apulian Bank is swept by strong currents of the Adriatic Deep Water Outflow. The temperature of 13.9 °C is the highest temperature recorded for L. pertusa and provides an important end-member of environmental conditions for geochemical analyses on living Atlantic and Mediterranean cold-water corals. Temperature and salinity (38.77 PSU) are stable throughout the year, and thus virtually no changes should be observed in the stable oxygen isotope signal-if the coral precipitates its skeleton in equilibrium with seawater. We measured various marine properties, such as the seawater oxygen isotope composition (δ18Osw), stable carbon isotope composition (δ13CDIC) of dissolved inorganic carbon (DIC), and dissolved inorganic nutrient concentrations (PO4, NO3, NO2, NH3 and SiO2). Bottom water at the coral sites shows a mean oxygen isotope composition of 1.47‰ δ18Osw-VSMOW, and δ13CDIC showed a mean of 1.1‰ VPDB. A section of a living L. pertusa with a thick theca calcification was probed with a Merchantek MicroMill at a high spatial sampling resolution with 10 samples per 1 mm. This reduced the signal-smoothing inherent to conventional sampling. The δ18Oag of coral aragonite ranges between -2.0‰ and +2.8‰ VPDB and the δ13Cag ranges between -7.77‰ and +1.47‰ VPDB. The Gaussian data distribution for both parameters, including heavy equilibrium values, suggests the completeness of the captured isotopic variability. The strict linear correlation of δ13C and δ18O displays a strong 'kinetic' vital effect. The intercept of the δ13C/δ18O correlation line with the δ13CDIC-composition permits recognition of δ18O equilibrium values of aragonite and thus reconstruction of water temperatures despite strong disequilibrium precipitation. Since the environmental parameters (T, S and δ18Osw) are stable, the entire isotopic signal of the coral must be driven by biological fractionation and might reflect growth speed variations, potentially related to pH variations and changes in the saturation state of the calcifying fluid or seasonally varying nutrient availability. Laser ablation tracks show a trace element composition dependent to microstructural zones (fibrous aragonite vs. centres of calcification). The parabolic relation of the classical temperature proxies Mg/Ca and U/Ca point to trace element vital effects, rendering them unreliable in L. pertusa. The P/Ca ratio shows similar values as Desmophyllum dianthus, for which a linear dependence with seawater phosphate (DIP) has been previously demonstrated. Consequently L. pertusa might be an additional nutrient recorder at bathyal depths. From the same site we also analysed the stable isotopic composition of the Last Glacial pectinid bivalve Pseudamussium peslutrae, which has been radiocarbon-dated (AMS-14C) at 26.3 ka 14C yr BP. The isotope values of the shell calcite document a strongly differing glacial temperature-salinity regime preceding the Holocene coral growth above a prominent hiatus. © 2009 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2010.nat.dgeo.IGM.LP.stable
Keywords: Cold-water corals; Lophelia pertusa; Stable isotopes; Trace elements; Vital effects